Lee Kuan Yew the grand master's insights on China, the United States, and the world - Lee, Kuan Yew 1923- (Belfer center studies in international security)
When Lee Kuan Yew speaks, presidents, prime ministers, diplomats, and CEOs listen. Lee the founding father of modern Singapore and its prime minister from 1959 to 1990 has honed his wisdom during more than fifty years on the world stage.